2019
DOI: 10.1177/0036933019897373
|View full text |Cite
|
Sign up to set email alerts
|

A case report of pancreatitis-panniculitis-polyarthritis syndrome – an unusual but serious presentation of pancreatic disease

Abstract: The clinical triad of peripheral cutaneous erythematous nodules, oligo or polyarthritis with intraosseous fat necrosis in the setting of pancreatic disease defines a rare entity called pancreatitis-panniculitis-polyarthritis syndrome. The early recognition of this triad is critical due to its high mortality rate and the rapid onset of osseous and articular disabilities. We describe the clinical course of a 54-year-old patient with complaints of weight loss and fever who presented to our hospital with signs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The clinical symptoms include a febrile state (or not), pain in multiple joints, swelling, and erythema in the affected areas. This syndrome is known as PPP syndrome (pancreatic disease, panniculitis and polyarthritis) [20] and was first described in 1908 by Berner [26]. A 2017 study by Dieker et al reported another 32 cases of this syndrome described in the literature in addition to their case report [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical symptoms include a febrile state (or not), pain in multiple joints, swelling, and erythema in the affected areas. This syndrome is known as PPP syndrome (pancreatic disease, panniculitis and polyarthritis) [20] and was first described in 1908 by Berner [26]. A 2017 study by Dieker et al reported another 32 cases of this syndrome described in the literature in addition to their case report [25].…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted theory that direct injury to the blood vessels by pancreatic enzymes and excessive release of circulating lipases in the course of pancreatitis results in fat necrosis and intramedullary lipolysis. Some researchers consider that inflammatory response and necrosis in articular areas are caused by free fatty acids which are formed by the hydrolysis of triglycerides under the action of pancreatic lipases [26]. Intra-abdominal fat necrosis of the retroperitoneum, mesentery, and omentum is a frequent complication of acute, chronic, and traumatic pancreatitis [1].…”
Section: Discussionmentioning
confidence: 99%